2018
DOI: 10.1103/physreva.98.023629
|View full text |Cite
|
Sign up to set email alerts
|

Optimal matter-wave gravimetry

Abstract: We calculate quantum and classical Fisher informations for gravity sensors based on matterwave interference, and find that current Mach-Zehnder interferometry is not optimally extracting the full metrological potential of these sensors. We show that by making measurements that resolve either the momentum or the position we can considerably improve the sensitivity. We also provide a simple modification that is capable of more than doubling the sensitivity. arXiv:1710.06340v3 [quant-ph]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 87 publications
(102 reference statements)
0
23
0
Order By: Relevance
“…Quantum metrology is an auspicious discipline of science where one makes high precision estimates of unknown parameters [1][2][3][4][5]. The field has numerous applications, including spectroscopy [6,7], magnetometry [8][9][10][11], thermometry [12,13] and gravimetry [14,15]. It has been known that utilizing quantum resources including entanglement allows one to achieve a gain in precision when compared to classical strategies [1,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum metrology is an auspicious discipline of science where one makes high precision estimates of unknown parameters [1][2][3][4][5]. The field has numerous applications, including spectroscopy [6,7], magnetometry [8][9][10][11], thermometry [12,13] and gravimetry [14,15]. It has been known that utilizing quantum resources including entanglement allows one to achieve a gain in precision when compared to classical strategies [1,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Because atoms have well-known properties and give reproducible measurements that can easily be related to SI units, they are ideal candidates for use in a new generation of sensors in the growing field of quantum technologies [20]. For example, atom-based sensors have been used for precise measurements of magnetic fields [21,22] and gravity [23,24] and are beginning to be marketed and used in fields as diverse as biomedical sensing [25], geomagnetic [26], and defense applications [27]. A subclass of atom-based sensors includes those based upon Rydberg atoms, atoms that have been excited to a high principal quantum number n. It has been shown that Rydberg atoms are excellent sensors for weak electromagnetic fields in the radio-frequency, microwave, and THz ranges [28][29][30][31], as well as for trace gas detection [32].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of interest has therefore developed in finding ways of improving their performance to gain advantage in different applications. It has been shown that Bose-condensed atomic sources can outperform thermal sources due to their narrow momentum linewidth, despite their reduced atomic flux [3][4][5][6][7]. The use of nonclassical atomic states such as spin-squeezed states can offset this reduction in flux even further by allowing for sensitivities beyond the shot-noise limit (SNL) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%